Legal Principles Against Gambling Establishments - Darma, Mospa (Legalpreneur Journal, 2024)
Gambling establishments are the root of the problem of gambling and become a source of other violations of the law.by the rules of criminal law with law No. 7 of 1974 on the control of gambling, gambling is a very clear action in the rule of Law Article 303 of the Criminal Code as a complement by its implementing regulations such as Government Regulation No. 9 of 1981 on the implementation of Law No. 7 of 1974 on the regulation of gambling. so that all actions related to gambling are strictly prohibited in Indonesian law, whether carried out by legal entities or government and private.Decisive action is the right step in the handling of gambling facilities and infrastructure. This research method using normative juridical methods.